Sustainable Triple‐A Supply Chains. Issue 3 (28th November 2020) - Erhun, Feryal; Kraft, Tim; Wijnsma, Sytske
Abstract : In his 2004 article, Professor Hau Lee argues that the best supply chains are not only fast and cost‐effective but also agile, adaptable, and aligned . The concept of triple‐A supply chains has been extensively studied in academic and trade publications and integrated into numerous operations and supply chain management curricula. It has also influenced the management approach of leaders around the world. Yet since the triple‐A concept was first developed, supply chains have become increasingly global, connected, and interdependent. The increased complexity of global supply chains has reduced much‐needed visibility, further complicating their management, while the growing connectivity and interdependence among different stakeholders have led to many unforeseen environmental and social issues. As a result, Professor Lee's emphasis on triple‐A supply chains is even more relevant today. In light of these new challenges and demands, we revisit the original triple‐A definitions of agile, adaptable, and aligned, expanding these concepts for a more socially and environmentally conscientious world. We also discuss potential enablers of and barriers to sustainable triple‐A supply chains.